Pembelajaran Keterampilan Berbicara dan Langkah-langkah Penyajian Dialog di Universitas Zainul Hasan Probolinggo - Ahmad Musthofa; Mamluatun Ni’mah (Alsina : Journal of Arabic Studies, 2021)
It is critical to developing speaking abilities while learning Arabic. The purpose of this article is to discuss several activities used to help students improve their speaking abilities at Zainul Hasan University, Probolinggo, Indonesia. The data were gathered via observation and interviews. The findings indicated that Zainul Hasan University students developed their speaking skills using a variety of activities, including memorization and dialogue practice, encouragement to speak, developing speaking Arabic habits, dialogue methods, and feedback on speaking errors. The dialogue method was proposed to develop Zainul Hasan University Probolinggo students' speaking abilities. It was arranged in the following steps: preliminary questions and answers, introduction of new vocabulary, comprehending new vocabulary, listening to the conversation while looking at the text, listening to dialogue without looking at the text, repetition of the dialogue's pronunciation, and in pair dialogue practice.